Magnetic resonance imaging and positron emission tomography in anti-NMDA receptor encephalitis: A systematic review. (June 2018) - Bacchi, Stephen; Franke, Kyle; Wewegama, Dasith; Needham, Edward; Patel, Sandy; Menon, David
Highlights: Fewer than half of MRIs in anti-NMDA receptor encephalitis show abnormal findings. Most common MRI abnormalities include T2 medial temporal and frontal hyperintensity. The only MRI finding with prognostic significance at this stage is progressive cerebellar atrophy. FDG-PET may demonstrate abnormalities in cases in which MRI does not. Future research should aim for larger sample sizes and report pre-imaging treatments. Abstract: Due to a variety of clinical manifestations anti-N-methyl-d -aspartate (NMDA) receptor encephalitis may be difficult to diagnose. Magnetic resonance imaging (MRI) may be used as a component of the workup for encephalopathy. However, the use of MRI in anti-NMDA encephalitis is complicated by wide-ranging reports regarding the frequency of normal MRI findings in this disease. Positron emission tomography (PET) is a modality of imaging that may assess functional rather than structural disturbances. Therefore, this review was conducted to summarise published studies regarding the use of MRI and PET in the diagnosis of anti-NMDA receptor encephalitis. The terms (MR OR magnetic resonance OR PET OR positron emission tomography) AND (NMDA encephalitis OR N-methyl-d -aspartate encephalitis) were used to search the databases PubMed, EMBASE and Scopus on 10/5/2017. These searches returned 1534 results. Sixty studies met the inclusion criteria. The results indicated that fewer than half of MRIs in anti-NMDA receptor encephalitis show abnormal findings. When abnormal findings are present they most commonly include T2/FLAIR medial temporal and frontal hyperintensity, and leptomeningeal contrast enhancement. Cortical grey matter changes were reported in the same number of patients as subcortical white matter changes. The only MRI finding with prognostic significance at this stage is progressive cerebellar atrophy. FDG-PET has been assessed in a few small studies and can demonstrate abnormalities in cases where MRI does not. Further research should aim for larger sample sizes and to report (and attempt to control for) the time between symptom onset and the scan being conducted, and pre-imaging treatments.